THE MECHANISM MODEL OF THE LOCOMOTIVE PANTOGRAPH AS A MECHANICAL SYSTEM WITH PNEUMATIC ACTUATOR - Babiak, M. O. (Science and Transport Progress, 2008)
In the model developed it is suggested in a generalized form the method of study of operation of the electric locomotive pantograph mechanism as mechanical system with pneumatic drive. The method has practically important features and can be realized on a computer.